PENGARUH PENALARAN SISWA TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI DALAM PEMBELAJARAN PjBL - Hilman Yusra (Universitas Wiralodra, 2022)
This study aims to examine (1) the effect of the PJBL model on students' ability to write descriptive text, (2) the effect of the PjBL model on the ability to write descriptive texts in students who have high reasoning, (3) the effect of PJBL on the ability to write descriptive texts in students who have reasoning. low, (4) the effect of reasoning on students' ability to write descriptive text. The approach used in this research is quantitative, which is carried out using a quasi-experimental method involving two variables. Determination of the sample is done randomly without regard to the existing strata in the population. Data was collected using multiple choice test instruments for reasoning abilities and performance tests for writing descriptive text skills. Data analysis was carried out by using a different test (t-test). The results of this study indicate (1) there is an effect of the PjBL model on students' ability to write descriptive text, (2) there is an effect of the PjBL model on the ability to write descriptive text in students who have high reasoning, (3) there is an effect of PjBL on the ability to write descriptive text in students. who have low reasoning, (4) there is an effect of reasoning on students' ability to write descriptive text. The PjBL model is better than the conventional model in learning outcomes, so the researcher suggests using the PjBL model in learning to write descriptions.